2020
DOI: 10.25299/dp.2020.vol36(1).5371
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Faktor Produksi Terhadap Produktivitas Usahatani Kelapa Sawit Pola Swadaya Di Desa Sungai Buluh Kecamatan Kuantan Singingi Hilir, Kabupaten Kuantan Singingi

Abstract: ABSTRACT Palm oil is one of the potential commodities that is widely cultivated by farmers in Singingi Hilir Regency. This study aims to analyze the farmers’ characteristics and profile of oil palm farming, the use of factors of production, costs, production, income and efficiency of oil palm farming, and the effect of production factors on oil palm farming productivity. The research was conducted during 6 months, starting from September 2018 to February 2019. Survey location was selected in Sungai Buluh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…One variable is called the dependent variable (Y), and the other is called the independent variable (X). The resolution of the relationship between X and Y is typically accomplished through regression, in which the variation of Y is influenced by variation in X [12]. Thus, the rules on the regression line also apply in the completion of the Cobb-Douglas function.…”
Section: Discussionmentioning
confidence: 99%
“…One variable is called the dependent variable (Y), and the other is called the independent variable (X). The resolution of the relationship between X and Y is typically accomplished through regression, in which the variation of Y is influenced by variation in X [12]. Thus, the rules on the regression line also apply in the completion of the Cobb-Douglas function.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, labor does not have a significant effect on productivity. According to Panjaitan et al (2020), Pasaribu et al (2016), it was found that N, P, MOP fertilisers has a significant effect on production. Meanwhile, labor has no significant effect on productivity.…”
Section: Estimation Of the Productivity Function Of Oil Palm Plantationsmentioning
confidence: 99%
“…Berikut adalah total produksi dan produktivitas tanaman kelapa sawit pada masa Menurut Siswanto, produktivitas kelapa sawit pola swadaya lebih rendah dari jumlah produktivitas kelapa sawit plasma (Siswanto et al, 2020). Sejalan dengan penelitian Edward Panjaitan yang menjelaskan bahwa petani kelapa sawit swadaya belum mengimplementasikan prinsip-prinsip dalam praktik budidaya dengan baik dan benar (Edward Panjaitan et al, 2020). Dalam menjalankan budidaya kelapa sawit, petani menerapkan praktik budidayanya dari ilmu yang diperoleh secara alami atau hasil diskusi bersama teman petani lainnya.…”
Section: Penggunaan Pupuk Sebelum Dan Sesudah Kenaikan Hargaunclassified